Management of addresses and road: Difficulties for the generation and integration of a georeferenced system - Copano-Ortiz, Luís (Revista de Estudios Andaluces, 2014)
The achievement of an integrated system of addresses will make possible geolocate any building or place likely to be inhabited or to host an economic activity, allowing for statistical information with disaggregation to level of portal. The future "Manager of Postal Addresses" is designed for that in the administrative records the address information only can interact with one of the stored in the spatial database. According to a study by EURADIN project, the availability of this system is going to allow a significant reduction in the costs of managing addresses obtaining an added value of 60,000 million euros per year, which has resulted in an increased interest on the part of public administration and economic sectors associated with new technologies.